Methods for determining the hardness of materials : Book 2 : Macro-, micro- and nano range : laboratory works No. 13-20 - Moshchenok, Vasyl; Lalazarova, Natalia; Moshchenok, Andrii (GlobeEdit, 2024)
The textbook presents 8 laboratory works on determining the surface, projection and volume hardness of metals measured with classical Brinell, Rockwell, Vickers hardness targets, as well as a study of indentation by the Berkovich pyramid in the nano- and micro-range using the Nano Test device. Each paper represents a complete scientific study that allows to significantly extend the functionality of modern hardness testers. For each method, the appropriate formulas have been developed and tested, and the research methodology is described in detail. These laboratory works are primarily aimed at postgraduate students and students of technical educational institutions but can also be used in metallurgical production and mechanical engineering to assess the quality of products using hardness testing methods. All the works have been tested over the past 10 years, have gained positive experience and can be recommended for active implementation in the educational process of technical universities.